Questionnaire d’aiguillage pour dépister les besoins de formation quant à l’offre active de services en français - Casimiro, Lynn; Savard, Jacinthe; Sauvé-Schenk, Katrine; Atchessi, Nicole (Reflets, 2018)
Des recherches antérieures montrent que certaines caractéristiques personnelles influencent la fréquence des comportements d’offre active des professionnelles et professionnels de la santé et du travail social. Un nouveau questionnaire d’aiguillage rempli par des étudiantes et étudiants de ces domaines aux niveaux collégial et universitaire a permis de déterminer leurs caractéristiques (profil sociolangagier) et de cibler des besoins en formation à l’offre active. Des formations en ligne, repérées parmi les formations déjà sur le Web, leur ont ensuite été proposées, en fonction de leur profil. Nos données montrent qu’il est possible de dresser des profils sociolangagiers utiles pour identifier des besoins de formation d’une manière acceptable pour les répondantes et répondants. Le type de formation qui répondra le mieux aux besoins de chaque profil reste à évaluer[1]. Mots-clés : offre active, formation des professionnelles et professionnels de la santé et des services sociaux, questionnaire d’aiguillage, francophones en situation minoritaire

Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)
fs-ref-orig: Savard, S., Savard, J., Benoît, J., Sauvé-Schenk, K., de Moissac, D., Durand, F., Dupuis-Blanchard, S. (2024). Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS), Université d'Ottawa. fs-code-orig: Savard-2024d